Prognostic significance of CD44 expression in adenocarcinoma of the lung. Issue 4 (August 1995) - Clarke, M R; Landreneau, R J; Resnick, N M; Crowley, R; Dougherty, G J; Cooper, D L; Yousem, S A
Abstract : Aims —To determine whether expression of CD44 in neoplasia is associated with tumour grade, stage and prognosis. Methods —The immunohistochemical expression of CD44 was evaluated using the mouse antihuman monoclonal antibody 3G12 which recognises regions shared by all CD44 isoforms to determine whether expression in formalin fixed, paraffin wax embedded tissue correlates with tumour grade, stage or survival in adenocarcinoma of the lung. Thirty one adenocarcinomas of the lung, 16 T2N0 and 15 T2N1, and their nodal metastases were studied. Results —Of the 31 tumours, 25 were positive for the CD44 antigen. CD44 expression correlated with tumour grade, in that intense staining was seen only in moderately and/or poorly differentiated tumours. CD44 did not correlate with nodal status, tumour size, pleural invasion, angiolymphatic invasion, or host inflammatory response, but did correlate with survival. A median survival of 46 months was observed in patients with moderate to strong CD44 expression compared with 24 months for those with no or weak expression. Nine patients were alive without evidence of disease at a median follow up of 61 months. Six (66%) of these nine patients had strong CD44 expression. This contrasts with strong expression in only three (17%) of the 17 patients dying with a median survival of 28 months. Conclusion —In primary adenocarcinoma of the lung loss of CD44 expression is associated with less favorable outcome and may indicate a more aggressive neoplasm. CD44 may be a useful prognostic marker in lung carcinoma.